Pendampingan Pembuatan Media Pembelajaran Berbasis Canva - Bani, Marsi; Ly, Petrus; Kollo, Fredik L.; Masud, Fadil; Uf., Soleman Nub (Neolectura, 2024)
Developing relevant learning media and learning resources in the classroom can optimize the learning process. For teachers, media helps concretize concepts or ideas and helps motivate active learning participants. For students, media can be a bridge for critical thinking and action. This training activity provides an opportunity for teachers to understand how to create Canva-based learning media. Participants in this activity were 15 teachers at the Cendana Abadi educational foundation at the primary and secondary education unit levels. The results achieved were that all teachers were able to understand and create Canva-based learning media.